Barriers to improving health care value in emergency general surgery: A nationwide analysis. Issue 2 (August 2020) - Hanna, Kamil; Haddadin, Zaid; Sakran, Joseph; Zeeshan, Muhammad; Asmar, Samer; Kulvatunyou, Narong; Tang, Andrew; Northcutt, Ashley; Joseph, Bellal
Abstract : INTRODUCTION: There is a growing need to improve the quality of care while decreasing health care costs in emergency general surgery (EGS). Health care value includes costs and quality and is a targeted metric by improvement programs. The aim of our study was to evaluate the trend of health care value in EGS over time and to identify barriers to high-value surgical care. METHODS: The (2012–2015) National Readmission Database was queried for patients 18 years or older who underwent an EGS procedure (according to the American Association for the Surgery of Trauma definition). Health care value ( V = quality metrics/cost) was calculated from the rates of freedom from readmission, major complications, reoperation, and failure to rescue (FTR) indexed over inflation-adjusted hospital costs. Outcomes were the trends in the quality metrics: 6-month readmission, major complications, reoperation, FTR, hospital costs, and health care value over the study period. Multivariable linear regression was performed to determine the predictors of lower health care value. RESULTS: We identified 887, 013 patients who underwent EGS. Mean ± SD age was 51 ± 20 years, and 53% were male. The rates of 6-month readmission, major complications, reoperation, and FTR increased significantly over the study period. The median hospital costs also increased over the study period (2012, US 9, 600 to 2015, US 13, 000; p < 0.01). However, the health care value has decreased over the study period (2012, 0.35; 2013, 0.30; 2014, 0.28; 2015, 0.25; p < 0.01). Predictors of decreased health care value in EGS are age 65 years or older ( β = −0.568 [−0.689 to −0.418], more than three comorbidities ( β = −0.292 [−0.359 to −0.21]), readmission to a different hospital ( β = −0.755 [−0.914 to −0.558]), admission to low volume centers ( β = −0.927 [−1.126 to −0.682]), lack of rehabilitation ( β = −0.004 [−0.005 to −0.003]), and admission on a weekend ( β = −0.318 [−0.366 to −0.254]). CONCLUSION: Health care value in EGS appears to be declining over time. Some of the factors leading to decreased health care value in EGS are potentially modifiable. Health care value could potentially be improved by reducing fragmentation of care and promoting regionalization. LEVEL OF EVIDENCE: Economic, level IV.